2013
DOI: 10.1002/aic.14033
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Methanol to Dimethoxymethane over Mesoporous Al‐P‐V‐O Catalysts

Abstract: The synthesis and application of bifunctional mesoporous Al‐P‐V—O catalysts with both acidic and redox sites for selective oxidation of methanol to dimethoxymethane (DMM) is described. The catalysts were characterized by N2 adsorption/desorption, X‐ray diffraction, temperature‐programmed desorption, X‐ray photoelectron spectroscopy, and infrared spectroscopy. It is shown that porosity; redox property and surface acidity of the catalysts were greatly influenced by the Al/V/P ratio. The synergistic effect of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…The NH 3 desorption peaks for Cu/ZSM-5(260) and Cu/ZSM-5(360) catalysts shifted to high temperatures compared to those for Cu/ZSM-5(25) catalysts, meaning that the acidity of the acid site became stronger with increasing silica content. For the Cu/b (25) catalysts, three NH 3 desorption peaks were observed in their NH 3 -TPD profiles, showing that the Cu/b(25) catalysts had weak-, medium-, and strong-strength acid sites. The acidities of the Cu/zeolite catalysts were calculated according to the areas of their NH 3 desorption peaks.…”
Section: Bet Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The NH 3 desorption peaks for Cu/ZSM-5(260) and Cu/ZSM-5(360) catalysts shifted to high temperatures compared to those for Cu/ZSM-5(25) catalysts, meaning that the acidity of the acid site became stronger with increasing silica content. For the Cu/b (25) catalysts, three NH 3 desorption peaks were observed in their NH 3 -TPD profiles, showing that the Cu/b(25) catalysts had weak-, medium-, and strong-strength acid sites. The acidities of the Cu/zeolite catalysts were calculated according to the areas of their NH 3 desorption peaks.…”
Section: Bet Analysismentioning
confidence: 99%
“…Then, MF was formed by the reaction between formaldehyde and methanol . The formation of MF from formaldehyde was rapid, and the formation of formaldehyde was the rate‐controlling step, which appeared to be a plausible explanation for the absence of formaldehyde in the products . Besides, DME could be produced by the intermolecular dehydration of methanol over acid sites.…”
Section: Coupling Reaction Between Methanol Dehydrogenation and Ma Hymentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports on vanadium‐based catalysts have been published and exemplarily, three examples will be considered in the following. A mesoporous bifunctional catalyst with the general composition Al‐P‐V‐O has been reported by Chen et al . It could be shown that there is a synergetic effect of phosphorous and vanadium, which has a significant influence on the redox and acid properties of the catalyst.…”
Section: Oxymethylene Dimethyl Ethers As Alternative Diesel Fuelsmentioning
confidence: 99%